African History Teaching in contemporary German textbooks: From biased knowledge to duty of remembrance (Yesterday & Today Journal for History Education in South Africa and abroad, 2021)
In early colonial times, European scientists explained and justified the aggressive and devastating expansion of Europe into nearly every corner of the world. Africans, for example, had been dehumanized, infantilized and bereft of history. The legacy of this manipulative enterprise can still be observed in various discourses of Africa in Western media and education. Induced into the Western cannon by Hegel, the notion of unhistorical Africa persists to the present day. Which role does contemporary education play in the manifestation of this ignorance? This paper analyses the role Africa occupies in German history textbook narratives. In only one of four textbook series, the existence of African history before the European “discovery” (the term is literally used by the books) is merely acknowledged. Others would not even explicitly (by text or maps) place Ancient Egypt in Africa, in accordance with Hegel. Pre-colonial Africa is absent from text, it can be sometimes found on the maps as a passive receiver of conquest or trade. The post-colonial history is largely reduced to the explanations of why Africa is “poor”. African sources and history archives are rarely used, priority is given to German or other Western sources. We argue that this persistent marginalization of Africa and Africans throughout the history curriculum in Germany needs to be urgently addressed by history educators and policy makers.
Keywords: German history textbooks; Racism; Representation of Africa; Critical Discourse Analysis